Selektive Vertriebssysteme am Fallbeispiel der Adidas AG - eine wettbewerbspolitische Beurteilung - Zindler, Finn

Kinderstärken – Kinder stärken: Pädagogische, soziologische und psychologische Zugänge zu einer „starken Idee" - Büker, Petra (Kinderstärken – Kinder stärken. Erziehung und Bildung ressourcenorientiert gestalten. (KinderStärken, Bd. 1))

KinderStärken beobachten und dokumentieren - Kordulla, Agnes; Büker, Petra (Kinderstärken – Kinder stärken. Erziehung und Bildung ressourcenorientiert gestalten. (KinderStärken, Bd. 1))

KinderStärken für das Aufwachsen in multikulturellen Lebenswelten - Hüpping, Birgit; Büker, Petra (Kinderstärken – Kinder stärken. Erziehung und Bildung ressourcenorientiert gestalten. (KinderStärken, Bd. 1))

Organisationsentwicklung und multiprofessionelle Teamarbeit im Kinderbildungshaus - eine systemische Perspektive - Bührmann, Thorsten; Büker, Petra (Diskurs Kindheits- und Jugendforschung)

Perspektiven von Kindern auf die Gestaltung didaktischer Lernarrangements im Übergang Kindergarten-Grundschule - Kordulla, Agnes; Büker, Petra (Perspektiven und Potentiale in der Schuleingangsstufe)

Inklusion vom Kind aus denken - das Vielfaltstableau für die Aus- und Weiterbildung in multi-professionellen Teams. Workshop im Rahmen der 3. Arbeitstagung der Multiplikatoren für Integration im Projekt ZINT an der Hochschule Görlitz/Zittau - Büker, Petra; Weiß, Christine
November 2015

Das Kind als kompetenter Akteur - Interdisziplinäre Anfragen an ein prominentes Paradigma der Früh- und Grundschulpädagogik. Vortrag an der Jahrestagung der Sektion Schulpädagogik der Deutschen Gesellschaft für Erziehungswissenschaft. Georg-August Universität Göttingen - Büker, Petra; Höke, Julia
September 2015

"This is important for us": Quality criterion enunciated by children as experts for their transition process from kindergarten to primary school. Poster presentation at the 25th EECERA conference - European Early Childhood Education Research Association. Barcelona, Spain - Büker, Petra; Bethke, Cathleen
September 2015

Inklusion vom Kind aus denken - eine Lehrerfortbildung mittels des Vielfaltstableaus gestalten: Vortrag im Rahmen des Praxisforums Inklusion des Bildungs- und Integrationszentrum des Kreises Paderborn in Kooperation mit der Universität Paderborn. Universität Paderborn - Büker, Petra; Weiß, Christine; Schulze Mengering, Theresia
September 2015

On the Tradeoff between Hardware Protection and Optimization Success: A Case Study in Onboard Evolutionary Robotics for Autonomous Parallel Parking - Wahby, Mostafa; Hamann, Heiko (Applications of Evolutionary Computation (EvoApplications 2015))

Flora Robotica - Mixed Societies of Symbiotic Robot-Plant Bio-Hybrids - Hamann, Heiko; Wahby, Mostafa; Schmickl, Thomas; Zahadat, Payam; Hofstadler, Daniel; Stoy, Kasper; Risi, Sebastian; Faina, Andres; Veenstra, Frank; Kernbach, Serge; Kuksin, Igor; Kernbach, Olga; et al. (Proceedings of the 2015 IEEE Symposium on Artificial Life (IEEE ALIFE'15))
Besides the life-as-it-could-be driver of artificial life research there is also the concept of extending natural life by creating hybrids or mixed societies that are built from natural and artificial components. In this paper we motivate and present the research program of the project flora robotica. Our objective is to develop and to investigate closely linked symbiotic relationships between robots and natural plants and to explore the potentials of a plant-robot society able to produce architectural artifacts and living spaces. These robot-plant bio-hybrids create synergies that allow for new functions of plants and robots. They also create novel design opportunities for an architecture that fuses the design and construction phase. The bio-hybrid is an example of mixed societies between 'hard' artificial and 'wet' natural life, which enables an interaction between natural and artificial ecologies. They form an embodied, self-organizing, and distributed cognitive system which is supposed to grow and develop over long periods of time resulting in the creation of meaningful architectural structures. A key idea is to assign equal roles to robots and plants in order to create a highly integrated, symbiotic system. Besides the gain of knowledge, this project has the objective to create a bio-hybrid system with a defined function and application -- growing architectural artifacts.

Lessons from Speciation Dynamics: How to Generate Selective Pressure Towards Diversity - Hamann, Heiko (Artificial Life)
Recent approaches in evolutionary robotics (ER) propose to generate behavioral diversity in order to evolve desired behaviors more easily. These approaches require the definition of a behavioral distance, which often includes task-specific features and hence a priori knowledge. Alternative methods, which do not explicitly force selective pressure towards diversity (SPTD) but still generate it, are known from the field of artificial life, such as in artificial ecologies (AEs). In this study, we investigate how SPTD is generated without task-specific behavioral features or other forms of a priori knowledge and detect how methods of generating SPTD can be transferred from the domain of AE to ER. A promising finding is that in both types of systems, in systems from ER that generate behavioral diversity and also in the investigated speciation model, selective pressure is generated towards unpopulated regions of search space. In a simple case study we investigate the practical implications of these findings and point to options for transferring the idea of self-organizing SPTD in AEs to the domain of ER.

Revisiting BEECLUST: Aggregation of Swarm Robots with Adaptiveness to Different Light Settings - Wahby, Mostafa; Weinhold, Alexander; Hamann, Heiko (Proceedings of the 9th EAI International Conference on Bio-inspired Information and Communications Technologies (formerly BIONETICS))
Aggregation is a crucial task in swarm robotics to ensure cooperation. We investigate the task of aggregation on an area specified indirectly by certain environmental features, here it is a light distribution. We extend the original BEECLUST algorithm, that implements an aggregation behavior, to an adaptive variant that automatically adapts to any light conditions. We compare these two control algorithms in a number of swarm robot experiments with different light conditions. The improved, adaptive variant is found to be significantly better in the tested setup.

Evolution of Controllers for Robot-Plant Bio-Hybdrids: A Simple Case Study Using a Model of Plant Growth and Motion - Wahby, Mostafa; Divband Soorati, Mohammad; von Mammen, Sebastian; Hamann, Heiko (Proceedings. 25. Computational Intelligence Workshop)

The Effect of Fitness Function Design on Performance in Evolutionary Robotics: The Influence of a Priori Knowledge - Hamann, Heiko; Divband Soorati, Mohammad (Proceedings of the Genetic and Evolutionary Computation Conference (GECCO 2015))
Fitness function design is known to be a critical feature of the evolutionary-robotics approach. Potentially, the complexity of evolving a successful controller for a given task can be reduced by integrating a priori knowledge into the fitness function which complicates the comparability of studies in evolutionary robotics. Still, there are only few publications that study the actual effects of different fitness functions on the robot's performance. In this paper, we follow the fitness function classification of Nelson et al. (2009) and investigate a selection of four classes of fitness functions that require different degrees of a priori knowledge. The robot controllers are evolved in simulation using NEAT and we investigate different tasks including obstacle avoidance and (periodic) goal homing. The best evolved controllers were then post-evaluated by examining their potential for adaptation, determining their convergence rates, and using cross-comparisons based on the different fitness function classes. The results confirm that the integration of more a priori knowledge can simplify a task and show that more attention should be paid to fitness function classes when comparing different studies.

Evolving Collective Behaviors With Diverse But Predictable Sensor States - Hamann, Heiko; Schmickl, Thomas; Zahadat, Payam (13th European Conference on Artificial Life (ECAL 2015))

Probabilistic Modeling of Swarming Systems - Hamann, Heiko; Correll, Nikolaus; Kacprzyk, Janusz; Pedrycz, Witold (Springer Handbook of Computational Intelligence)

Dependability in Swarm Robotics: Error Detection and Correction - Ding, Hongli; Hamann, Heiko (First International Symposium on Swarm Behavior and Bio-Inspired Robotics (SWARM 2015))

Potential of Heterogeneity in Collective Behaviors: A Case Study on Heterogeneous Swarms - Hamann, Heiko; Schmickl, Thomas; Kengyel, Daniela; Zahadat, Payam; Radspieler, Gerald; Wotawa, Franz (Principles and Practice of Multi-Agent Systems (PRIMA 2015))

Time-variant feedback processes in collective decision-making systems: influence and effect of dynamic neighborhood sizes - Valentini, Gabriele; Hamann, Heiko (Swarm Intelligence)

Efficient Decision-Making in a Self-Organizing Robot Swarm: On the Speed Versus Accuracy Trade-Off - Dorigo, Marco; Hamann, Heiko; Valentini, Gabriele (Proceedings of the 14th Int. Conf. on Autonomous Agents and Multiagent Systems (AAMAS 2015))

Self-organized collective decisions in a robot swarm - Dorigo, Marco; Hamann, Heiko; Valentini, Gabriele (AAAI-15 Video Proceedings)

Optimized method in sizing of Flapping Wing - Kaveh, Mahdi; Pourmohammad, Javad; Hassanalian, Mostafa; Nili Ahmadabadi, Mahdi; Otroshi, Mortaza

Market-Specific Service Compositions: Specification and Matching - Arifulina, Svetlana; Platenius, Marie Christin; Mohr, Felix; Engels, Gregor; Schäfer, Wilhelm (Proceedings of the IEEE 11th World Congress on Services (SERVICES), Visionary Track: Service Composition for the Future Internet)
The Collaborative Research Centre "On-The-Fly Computing" works on foundations and principles for the vision of the Future Internet. It proposes the paradigm of On-The-Fly Computing, which tackles emerging worldwide service markets. In these markets, service providers trade software, platform, and infrastructure as a service. Service requesters state requirements on services. To satisfy these requirements, the new role of brokers, who are (human) actors building service compositions on the fly, is introduced. Brokers have to specify service compositions formally and comprehensively using a domain-specific language (DSL), and to use service matching for the discovery of the constituent services available in the market. The broker's choice of the DSL and matching approaches influences her success of building compositions as distinctive properties of different service markets play a significant role. In this paper, we propose a new approach of engineering a situation-specific DSL by customizing a comprehensive, modular DSL and its matching for given service market properties. This enables the broker to create market-specific composition specifications and to perform market-specific service matching. As a result, the broker builds service compositions satisfying the requester's requirements more accurately. We evaluated the presented concepts using case studies in service markets for tourism and university management.

Changes in dietary intake during puberty and their determinants: results from the GINIplus birth cohort study - Harris, Carla; Flexeder, Claudia; Thiering, Elisabeth; Buyken, Anette; Berdel, Dietrich; Koletzko, Sibylle; Bauer, Carl-Peter; Brüske, Irene; Koletzko, Berthold; Standl, Marie (BMC Public Health)
Background Understanding changes in dietary intake during puberty could aid the mapping of dietary interventions for primary prevention. The present study describes dietary changes from childhood to adolescence, and their associations with parental education, family income, child education, body mass index (BMI), pubertal onset and screen-time sedentary behaviour. Methods Dietary data (n = 1232) were obtained from food frequency questionnaires at the 10- and 15-year follow-ups of the GINIplus birth cohort study. Intakes of 17 food groups, macronutrients and antioxidant vitamins, were described by a) paired Wilcoxon rank sum tests, comparing average intakes at each time-point, and b) Cohen’s kappa “tracking” coefficients, measuring stability of intakes (maintenance of relative tertile positions across time). Further, associations of changes (tertile position increase or decrease vs. tracking) with parental education, family income, child education, pubertal onset, BMI, and screen-time, were assessed by logistic regression and multinomial logistic regression models stratified by baseline intake tertile. Results Both sexes increased average intakes of water and decreased starchy vegetables, margarine and dairy. Females decreased meat and retinol intakes and increased vegetables, grains, oils and tea. Males decreased fruit and carbohydrates and increased average intakes of meat, caloric drinks, water, protein, fat, polyunsaturated fatty acids (PUFAs), vitamin C and alpha-tocopherol. Both sexes presented mainly “fair” tracking levels [κw = 0.21–0.40]. Females with high (vs. low) parental education were more likely to increase their nut intake [OR = 3.8; 95 % CI = (1.7;8.8)], and less likely to decrease vitamin C intakes [0.2 (0.1;0.5)], while males were less likely to increase egg consumption [0.2 (0.1;0.5)] and n3 PUFAs [0.2 (0.1;0.5)]. Females with a higher (vs. low) family income were more likely to maintain medium wholegrain intakes [0.2 (0.1;0.7) for decrease vs. tracking, and 0.1 (0.0;0.5) for increase vs. tracking], and were less likely to decrease vitamin C intakes [0.2 (0.1;0.6)]. Males with high education were less likely to increase sugar-sweetened foods [0.1 (0.1;0.4)]. Finally, BMI in females was negatively associated with decreasing protein intakes [0.7 (0.6;0.9)]. In males BMI was positively associated with increasing margarine [1.4 (1.1;1.6)] and vitamin C intakes [1.4 (1.1;1.6)], and negatively associated with increasing n3 PUFA. Conclusions Average dietary intakes changed significantly, despite fair tracking levels, suggesting the presence of trends in dietary behaviour during puberty. Family income and parental education predominantly influenced intake changes. Our results support the rationale for dietary interventions targeting children, and suggest that sex-specific subpopulations, e.g. low socio-economic status, should be considered for added impact.
Keywords: Puberty; Dietary intake; Dietary changes; Tracking; Determinants; Epidemiology

Lernpotential durch Lehrerkooperation. Vorstellung eines Analyseansatzes zur Erfassung erfahrungsbezogener Lerngelegenheiten. - Bloh, Thiemo; Bloh, Bea; van Ophuysen, Stefanie (Empirische Pädagogik)

Load Balancing for Range Queries in a Dimension Invariant Peer-to-Peer Network - Rojahn, Tobias

Playing the Lottery or Dressing Up? A Model of Firm-Level Heterogeneity and the Decision to Export - Gries, Thomas; Naudé, Wim; Bilkic, Natascha (The Quarterly Review of Economics and Finance)

Changes of China’s agri-food exports to Germany caused by its accession to WTO and the 2008 financial crisis - Gries, Thomas; Feng, Yuanhua; Guo, Zhichao (China Agricultural Economic Review)

Koordinierter Patentschutz in einer globalisierten Welt - Effizienz- und Anreizwirkungen auf die Arzneimittelversorgung in Entwicklungsländern - Kirsch, Michelle

Expertensystem zur Steigerung der Effizienz im Bereich der Produktion - Iwanek, Peter; Dumitrescu, Roman; Reinhart, Felix; Brandis, Rinje (productivITy (4 / 2015))

Economics and Value of IS - Han, K.; Kundisch, Dennis; Weinhardt, C.; Zimmermann, Steffen

Planungswerkzeug zur wissensbasierten Produktionssystemkonzipierung - Bauer, Frank

10. Paderborner Workshop Entwurf mechatronischer Systeme - Gausemeier, Jürgen; Dumitrescu, Roman; Rammig, Franz-Josef; Schäfer, Wilhelm; Trächtler, Ansgar

Vorausschau und Technologieplanung. 11. Symposium für Vorausschau und Technologieplanung, Heinz Nixdorf Institut, 29. und 30. Oktober 2015 - Gausemeier, Jürgen

Just test what you cannot verify! - Czech, Mike; Jakobs, Marie-Christine; Wehrheim, Heike (Fundamental Approaches to Software Engineering)
Today, software verification is an established analysis method which can provide high guarantees for software safety. However, the resources (time and/or memory) for an exhaustive verification are not always available, and analysis then has to resort to other techniques, like testing. Most often, the already achieved partial verification results arediscarded in this case, and testing has to start from scratch.In this paper, we propose a method for combining verification and testing in which testing only needs to check the residual fraction of an uncompleted verification. To this end, the partial results of a verification run are used to construct a residual program (and residual assertions to be checked on it). The residual program can afterwards be fed into standardtesting tools. The proposed technique is sound modulo the soundness of the testing procedure. Experimental results show that this combinedusage of verification and testing can significantly reduce the effort for the subsequent testing.

ARTiST - An Augmented Reality Testbed for Intelligent Technical Systems - Hassan, Bassem; Stöcklein, Jörg; Berssenbrügge, Jan (Virtual, Augmented and Mixed Reality VAMR 2015 Held as Part of HCI International 2015; LNCS 9179)

Der Mensch als Vorbild - Trächtler, Ansgar; Iwanek, Peter; Scheffels, Gerald (elektrotechnik - Automatisierung Sonderausgabe)

Integrated Systems Engineering and Software Requirements Engineering for Technical Systems - Holtmann, Jörg; Bernijazov, Ruslan; Meyer, Matthias; Schmelter, David; Tschirner, Christian (Proceedings of the International Conference on Software and Systems Process (ICSSP))
The development of software-intensive technical systems (e.g., within the automotive industry) involves several engineering disciplines like mechanical, electrical, control, and software engineering. Model-based Systems Engineering (MBSE) coordinates these disciplines throughout the development by means of discipline-spanning processes and system models. Such a system model provides a common understanding of the system under development and serves as a starting point for the discipline-specific development. An integral part of MBSE is the requirements engineering on the system level. However, for the discipline-specific development to start, these requirements need to be refined, e.g., into specific requirements for the embedded software. Since existing MBSE approaches lack support for this refinement step, we conceived a systematic transition from MBSE to model-based software requirements engineering, which we present in this paper. We automated the steps of the transition where possible, in order to avoid error-prone and time-consuming manual tasks. We illustrate the approach with an example of an automotive embedded system.

Planning and Optimisation of Manufacturing Process Chains for Functionally Graded Components – Part 2: Case Study on Self-reinforced Thermoplastic Composites - Biermann, Dirk; Gausemeier, Jürgen; Heim, Hans-Peter; Hess, Stefan; Petersen, Marcus; Ries, Angela; Wagner, T. (Production Engineering Research & Development 9(3))
In this sequel paper, the previously presented framework for the planning and optimisation of functionally graded components Biermann et al. (Production Engineering Research & Development 7(6):657–664, 2013) is applied within a case study. In addition to the application, the implementational infrastructure of the framework is provided and the preliminaries for applying the framework to the respective production system are presented. Hence, the practical realisation of the models and methods is documented. In the context of the case study, each step of the planning process is demonstrated in a visually assisted way. These visualisations are based on the specific steps of the wizard guiding the planner through the framework. As a central contribution, the specification of a non-trivial gradation and the planning of the corresponding process chain by means of the planning framework are demonstrated.

Visualization of Headlight Illumination for the Virtual Prototyping of Light-Based Driver Assistance Systems - Berssenbrügge, Jan; Trächtler, Ansgar; Schmidt, Christoph (Proceedings of the ASME 2015 International Design Engineering Technical Conferences & Computers and Information in Engineering Conference)

Zustandsorientierte Modellierung flexibler Produktionssysteme - Bremer, Christian; Dumitrescu, Roman; Gausemeier, Jürgen (Stuttgarter Symposium für Produktentwicklung - SSP 2015)

Ontology-based determination of alternative CNC machines for a flexible resource allocation - Rehage, Gerald; Gausemeier, Jürgen (15th CIRP Conference on Modelling of Machining Operations (15th CMMO), Band 31)
In case of an unplanned machine breakdown, alternative resources have to be found quickly to avoid delays in following process steps. In order to counter this, an automated determination of alternative CNC-machines and a reliable validation is proposed. First, a rough process description is extracted from the NC program. Second, a suitable machine is searched in an ontology based on the rough process description. The ontology contains a description of all needed properties of a machine and rules to derive the resulting capabilities. Third, the NC program is validated on a virtual machine to ensure the absence of errors.

Vorsprung durch strategisches IP-Management - Gestiges Eigentum kennen, schützen und nutzen - Eckelt, Daniel; Gausemeier, Jürgen (IP: Kooperation, Wettbewerb, Konfrontation, 37. Kollequium der TU Ilmenau über Patentinformationen, Band 37)

Balancing the Strategic Product Portfolio based on Market and Competence Needs - Rübbelke, René; Söllner, Christoph; Gausemeier, Jürgen (24th International Association for Management of Technology Conference, Nr. 24)

Conception of a Knowledge Management System for Technologies - Placzek, Markus; Eberling, Christian; Gausemeier, Jürgen (24th International Association for Management of Technology Conference Proceedings, Band 24)

Tagungsband zum Stuttgarter Symposium für Produktentwicklung (SSP) - Amshoff, Benjamin; Dülme, Christian; Echterfeld, Julian; Gausemeier, Jürgen

BUSINESS MODEL PATTERNS FOR DISRUPTIVE TECHNOLOGIES - Amshoff, Benjamin; Dülme, Christian; Echterfeld, Julian; Gausemeier, Jürgen (International Journal of Innovation Management 19(3))

HOW TO USE BUSINESS MODEL PATTERNS FOR EXPLOITING DISRUPTIVE TECHNOLOGIES - Echterfeld, Julian; Amshoff, Benjamin; Gausemeier, Jürgen (International Association for Management of Technology (IAMOT))

Modellorientierte Vernetzung von Strategischer Produktplanung und Produktentwicklung - Wiederkehr, Olga; Echterfeld, Julian; Gausemeier, Jürgen; Lehner, Anne-Christin (Stuttgarter Symposium für Produktentwicklung (SSP) 2015)

A Modular Architecture of an Interactive Simulation and Training Environment for Advanced Driver Assistance Systems - Abdelgawad, Kareem; Hassan, Bassem; Berssenbrügge, Jan; Stöcklein, Jörg; Grafe, Michael (International Journal On Advances in Software, Band 8)

Challenges in Anti-Counterfeiting of Cyber-Physical Systems - Kliewe, Daniel; Kühn, Arno; Dumitrescu, Roman; Gausemeier, Jürgen (International Science Index, Band 9-5)
his paper examines the system protection for cyber-physical systems (CPS). CPS are particularly characterized by their networking system components. This means they are able to adapt to the needs of their users and its environment. With this ability, CPS have new, specific requirements on the protection against anti-counterfeiting, know-how loss and manipulation. They increase the requirements on system protection because piracy attacks can be more diverse, for example because of an increasing number of interfaces or through the networking abilities. The new requirements were identified and in a next step matched with existing protective measures. Due to the found gap the development of new protection measures has to be forced to close this gap. Moreover a comparison of the effectiveness between selected measures was realized and the first results are presented in this paper.

Anbindung des Virtuellen Prototypen an die Partialmodelle intelligenter technischer Systeme - Berssenbrügge, Jan; Wiederkehr, Olga; Jähn, Claudius; Fischer, Matthias (12. Paderborner Workshop Augmented & Virtual Reality in der Produktentstehung, Band 342)

Visualisierung von Scheinwerfersystemen für das Virtual Prototyping von lichtbasierten Fahrerassistenzsystemen - Berssenbrügge, Jan; Trächtler, Ansgar; Schmidt, Christoph; Stöcklein, Jörg; Grafe, Michael (12. Paderborner Workshop Augmented & Virtual Reality in der Produktentstehung, Band 342)

Systematik für die Entwicklung von rekonfigurierbaren Fahrsimulatoren - Hassan, Bassem; Gausemeier, Jürgen; Abdelgawad, Kareem; Berssenbrügge, Jan; Grafe, Michael (12. Paderborner Workshop Augmented & Virtual Reality in der Produktentstehung, Band 342)

Wissensaufbereitung und -bereitstellung durch Ontologien im Lebenszyklus von Produktionssystemen - Petersen, Marcus; Rehage, Gerald; Gausemeier, Jürgen; Bauer, Frank (Wissenschafts- und Industrieforum 2015 Intelligente Technische Systeme - 10. Paderborner Workshop Entwurf mechatronischer Systeme, Nr. 343)
Der Lebenszyklus von Produktionssystemen besteht nach Wiendahl et al. aus den drei Phasen Planung und Realisierung, Betrieb und Redistribution (Wiendahl et al. in Anlaufrobuste Produktionssysteme. Werkstattstechnik (wt) online, Jahrg. 92, Ausgabe 11/12, 2002, S. 650-655). Jede Phase enthält vielfältige Aufgaben die maßgeblich vom Fach- und Erfahrungswissen der Mitarbeiter abhängen. In der ersten Phase werden unter anderem die Fertigungsprozesse und -ressourcen festgelegt. Hierfür bedarf es genauer Kenntnisse über die zu fertigenden Bauteile, benötigten Prozesse und geeigneten Ressourcen selbst sowie deren Abhängigkeiten untereinander. In der Betriebsphase des Produktionssystems muss auf Maschinenausfälle oder Eilaufträge mit Um- bzw. Neuplanungen von Ressourcen reagiert werden. Das benötigte Wissen im Lebenszyklus von Produktionssystemen verteilt sich in der Regel auf verschiedene Personen und eine Vielzahl unterschiedlicher Dokumente; teilweise ist es auch nur implizit vorhanden. Demzufolge liegt es verteilt und unstrukturiert vor und eignet sich nicht für eine bedarfsgerechte Bereitstellung. Darüber hinaus fehlt eine Semantik, die das vorhandene Wissen in Beziehung setzt und durch automatisierte Schlussfolgerungen ergänzt. Hierfür bieten wissensbasierte Systeme (WBS) auf Basis von Ontologien einen vielversprechenden Lösungsansatz. Diese bieten eine Semantik und Inferenz zur Wissensmodellierung und ermöglichen den effizienten Zugriff auf das benötigte Wissen. Dies verspricht eine große Zeitersparnis bei den Aufgaben im Lebenszyklus von Produktionssystemen, auch im Hinblick auf die immer kürzer werdenden Produktlebenszyklen. Der Beitrag beschreibt den Aufbau von drei Ontologien für das Wissensmanagement im Rahmen verschiedener Aufgaben. Ferner werden die Vorteile durch den Einsatz von Ontologien praxisorientiert anhand eines Produktionssystems für eine Taschenlampe dargestellt.

Automatische Ableitung geometrischer Eigenschaften von Bauteilen aus dem 3-D-Polygonmodell - Jähn, Claudius; Fischer, Matthias; Gerges, Maria; Berssenbrügge, Jan (12. Paderborner Workshop Augmented & Virtual Reality in der Produktentstehung, Band 342)

Innovationspotentiale auf dem Weg zu Industrie 4.0 - Gausemeier, Jürgen; Czaja, Anja; Dülme, Christian (Wissenschafts- und Industrieforum Intelligente Technische Systeme 2015 10. Paderborner Workshop Entwurf mechatronischer Systeme, Band 343)

Virtuelle Inbetriebnahme mit wählbarer Modellierungstiefe - Frieben, Tanja; Schneider, Marcel; Gausemeier, Jürgen; Trächtler, Ansgar (ZWF Zeitschrift für wirtschaftlichen Fabrikbetrieb 110(4))

Augmented & Virtual Reality in der Produktentstehung: Grundlagen, Methoden und Werkzeuge; Interaktions- und Visualisierungstechniken, Virtual Prototyping intelligenter technischer Systeme mit AR/VR

Industrie 4.0 – Dezentralisierung bestehender Produktionssysteme durch kostengünstige Einplatinenrechner - Petersen, Marcus; Gausemeier, Jürgen; Köchling, Daniel; Schneider, Marcel; Wellpott, Marcel (24. Deutscher Materialfluss-Kongress mit VDI-Konferenz Shuttle in der Logistik, VDI-Berichte, Band 2234)
Das Paradigma Industrie 4.0 bietet produzierenden Unternehmen große Potentiale hinsichtlich Flexibilitäts- und Produktivitätssteigerungen. Bei der Umsetzung des Paradigmas stehen die Unternehmen jedoch häufig vor der Herausforderung bestehende Produktionssysteme dezentralisieren und mit einer inhärenten Intelligenz nachrüsten zu müssen. Hierfür existieren allerdings noch keine fertigen "Out of the box"-Lösungen, sodass hohe Investitionskosten für die Konzeption und Inbetriebnahme kundenspezifischer Lösungen entstehen. Kosten die kleine und mittlere Unternehmen (KMU) häufig nicht aufbringen können, wodurch ihnen die Umsetzung von Industrie 4.0 wesentlich erschwert wird. Vor diesem Hintergrund besteht ein erheblicher Bedarf an kostengünstigen Ansätzen für den Einstieg in Industrie 4.0. In diesem Beitrag wird ein Konzept zur Dezentralisierung bestehender Produktionssysteme auf Basis kostengünstiger Einplatinenrechner (engl.: Single Board Computer) am Beispiel des Raspberry Pi vorgestellt. Dabei wird jede Komponente eines bestehenden Produktionssystems mit einem Einplatinenrechner bestückt, der anschließend die Anbindung der Komponente an das Produktionsnetzwerk, dessen Rolle sowie die dafür notwendige Datenverarbeitung regelt. Zudem übernimmt der Einplatinenrechner die Kommunikation der Komponente innerhalb des gesamten Netzwerks. Das Konzept umfasst eine Kommunikationsarchitektur für ein Produktionsnetzwerk sowie die darauf aufbauende dezentrale Materialflusssteuerung. Die Absicherung erfolgt anhand von Materialflusssimulationen. Notwendige Erweiterungsmaßnahmen, wie bspw. die Anbindung der SBC an die Produktionsressourcen, zur Umsetzung des Konzepts runden den Beitrag ab.

Identifikation von Potentialen zur Integration von Lösungen der Selbstoptimierung für technische Systeme des Maschinen- und Anlagenbaus - Iwanek, Peter; Dumitrescu, Roman; Gausemeier, Jürgen (VDI Mechatroniktagung 2015)

Systematische Vernetzung von Strategischer Produktplanung und Produktentwicklung - Wiederkehr, Olga; Dumitrescu, Roman; Gausemeier, Jürgen (VDI Mechatroniktagung 2015)

Planung der Inbetriebnahme mechatronischer Prototypen auf Basis einer disziplinübergreifenden Systemmodellierung - Weisske, Alexander; Iwanek, Peter; Flottmeier, Sarah; Czaja, Anja; Trächtler, Ansgar; Dumitrescu, Roman (VDI Mechatroniktagung 2015)

Systematik zur wirtschaftlichkeitsorientierten Konzipierung Intelligenter Technischer Systeme - Vaßholz, Mareen

Systematik zur Entwicklung einer produktlebenszyklusorientierten Geschäftsmodell-Roadmap - Peitz, Christoph

Systematik zur frühzeitigen Absicherung der Sicherheit und Zuverlässigkeit fortschrittlicher mechatronischer Systeme - Dorociak, Rafal

Vorausschau von Stakeholder-Verhalten mit der Szenario-Technik - Peter, Stefan; Gausemeier, Jürgen; Amshoff, Benjamin; Koldewey, Christian (Symposium für Vorausschau und Technologieplanung, Band 347 , Kapitel: 1)
Strategische Planung ermöglicht es, frühzeitig auf sich ändernde Markt- und Wettbe-werbsbedingungen zu reagieren. Für strategische Entscheidungen wird eine Vorstellung von der Zukunft benötigt. Das zukünftige Verhalten von Wettbewerbern, Lieferanten, Kunden, Verbänden etc. (Stakeholder) ist dabei eine wesentliche Einflussgröße. Dies birgt große Unsicherheit bzgl. konkreter Entscheidungsprobleme (z.B. Produktstrategie: Wie soll der Wettbewerbsvorsprung über die Produktlebensdauer erhalten bleiben?). Wie diese Stakeholder auf strategische Entscheidungen reagieren, lässt sich allerdings nicht ohne weiteres vorhersagen (z.B. Preiskampf, Innovations-Offensive). Das Fortschreiben bisherigen Verhaltens kann zu Fehleinschätzungen führen. Somit ist es notwendig das Verhalten der relevanten Stakeholder systematisch vorauszudenken. Dabei hilft die Szenario-Technik mögliche Reaktionen zu antizipieren. Wir schlagen ein Vorgehen vor, das sich aus Stakeholder-Analyse und Szenario-Technik zusammensetzt. Dabei zeigen wir, wie Stakeholder identifiziert werden, die den größten Einfluss auf den Erfolg der gewählten Entscheidung haben. Dabei spielen Reaktions-neigung und Betroffenheit eine wesentliche Rolle. Für die relevanten Stakeholder wer-den Verhaltens-Szenarien erstellt. Dazu können ausgehend von einem Katalog Positio-nierungsvariablen mit unterschiedlichen Handlungsoptionen ausgewählt und um situati-onsbedingte Variablen angereichert werden. Die Verhaltens-Szenarien geben Aufschluss über mögliche, konsistente Verhaltensweisen der Stakeholder. Abschließend erläutern wir, wie Referenz-Szenarien auf Basis des Stakeholder-Charakters ausgewählt werden und wie daraus Rückschlüsse für die eigene Entscheidung getroffen werden können.

Systematik zur Kostenbewertung von mechatronischen Systemen in der Technologie Molded Interconnect Devices - Schierbaum, Thomas; Gausemeier, Jürgen (Wissenschafts- und Industrieforum 2015 Intelligente Technische Systeme - 10. Paderborner Workshop Entwurf mechatronischer Systeme)

Der Klang meines Selbst: Aussprache und Selbstkonstruktion von Fremdsprachenlernenden - Müller, Mareike; Schmenk, Barbara (Konzepte aus der Sprachlehrforschung – Impulse für die Praxis: Festschrift für Karin Kleppin)
Dieser Beitrag untersucht den Einfluss der Aussprache auf die Selbstkonstruktion von Lernenden und deren Bereitschaft, sich auf die zu erlernende Sprache und Kultur einzulassen. Im Gegensatz zu traditionellen Forschungsansätzen wird die Aussprache dabei als subjektiv bedeutsame Dimension im Sprachlernprozess konzipiert, die die Wahrnehmungen der Lernenden gegenüber sich selbst, anderen Sprechenden und dem gesamten Lernkontext stark mitprägt. Die Untersuchungen basieren auf den Narrationen zweier kanadischer Germanistikstudierender, die zwei Semester an deutschen Universitäten verbrachten. Der Selbstfindungs- und Lernprozess beider Studierender im fremden Umfeld wird dabei wesentlich durch ihre Selbstwahrnehmungen gelenkt, welche wiederum stark um das Thema Aussprache kreisen. Obwohl sich beide Lernende sehr unterschiedlich als Sprechende des Deutschen konstruieren, fixieren sie sich darauf, wie sie meinen zu klingen und folglich wahrgenommen zu werden. Dabei erweist sich vor allem das Konstrukt des Native Speaker als zentraler Vergleichspunkt, an dem sich die Lernenden messen und der somit als Basis für die Wertung des Auslandsaufenthalts und des eigenen Lernerfolgs dient. Durch die Analyse subjektiver Lernertheorien entwirft dieser Beitrag einen gänzlich neuen Rahmen für die Betrachtung von Aussprache im Sprachlernprozess, der über die rein phonetische Dimension hinausgeht und den Fokus auf die sozialpsychologischen Funktionen von Aussprache lenkt.

IRIS: A Robust Information System Against Insider DoS Attacks - Eikel, Martina; Scheideler, Christian (Transactions on Parallel Computing)
In this work, we present the first scalable distributed information system, that is, a system with low storage overhead, that is provably robust against denial-of-service (DoS) attacks by a current insider. We allow a current insider to have complete knowledge about the information system and to have the power to block any ϵ-fraction of its servers by a DoS attack, where ϵ can be chosen up to a constant. The task of the system is to serve any collection of lookup requests with at most one per nonblocked server in an efficient way despite this attack. Previously, scalable solutions were only known for DoS attacks of past insiders, where a past insider only has complete knowledge about some past time point t0 of the information system. Scheideler et al. [Awerbuch and Scheideler 2007; Baumgart et al. 2009] showed that in this case, it is possible to design an information system so that any information that was inserted or last updated after t0 is safe against a DoS attack. But their constructions would not work at all for a current insider. The key idea behind our IRIS system is to make extensive use of coding. More precisely, we present two alternative distributed coding strategies with an at most logarithmic storage overhead that can handle up to a constant fraction of blocked servers.

„Forschendes Lernen“ im Praxissemester – Präkonzepte und Überzeugungen von Lehramtsstudierenden - Homt, Martina; van Ophuysen, Stefanie

Qualitätskriterien für den Einsatz von Dokumentationsinstrumenten im Kontext des Grundschulübergangs - Homt, Martina; Riek, Kim; van Ophuysen, Stefanie

„Forschendes Lernen“ im Praxissemester – Konzeption und erste Evaluation der Methodenausbildung für Lehramtsstudierende an der WWU Münster - Schmidt, Jennifer; Homt, Martina; Behrmann, Lars; van Ophuysen, Stefanie

Incremental Inductive Verification of Parameterized Timed Systems - Isenberg, Tobias (Proceedings of the 15th International Conference on Application of Concurrency to System Design (ACSD))
We propose an incremental workflow for the verification of parameterized systems modeled as symmetric networks of timed automata. Starting with a small number of timed automata in the network, a safety property is verified using IC3, a state-of-the-art algorithm based on induction.The result of the verification, an inductive strengthening, is reused proposing a candidate inductive strengthening for a larger network.If the candidate is valid, our main theorem states that the safety property holds for all sizes of the network of timed automata. Otherwise the number of automata is increased and the next iteration is started with a new run of IC3.We propose and thoroughly examine optimizations to our workflow, e.g. Feedback mechanisms to speed up the run of IC3.

Die Steuerungsfunktion von zentralen Abiturprüfungen – Analysen und kontroverse Einschätzungen der Aufgabenschwierigkeit und mögliche Rückkopplungen auf den Unterricht - Kahnert, Julia; Eickelmann, Birgit; Lorenz, Ramona; Bos, Wilfried (Governance im Bildungswesen zwischen Steuerung, Koordination und Marktgeschehen)

Impulse für eine Schule der Zukunft – Zentrale Ergebnisse der internationalen Schulleistungsstudie ICILS 2013 - Eickelmann, Birgit; Gerick, Julia; Bos, Wilfried (Zeitschrift Schul-Management)

Vermittlung digitaler Kompetenzen als neues Handlungsfeld für Schulen und Schulleitungen. Zentrale Ergebnisse der internationalen Schulleistungsstudie ICILS 2013 - Gerick, Julia; Eickelmann, Birgit; Bos, Wilfried (Digitale Medien in der Schule)

Bildungsgerechtigkeit 4.0 - ICILS 2013: Grundlage für eine neue Debatte zur Bildungsgerechtigkeit - Eickelmann, Birgit

Lehrerprofessionalisierung und Fortbildungsaktivitäten im Kontext von Schulentwicklung mit neuen Technologien - Gerick, Julia; Eickelmann, Birgit (Journal für Schulentwicklung)

Preparing teachers for schooling in the digital age: A meta-perspective on existing strategies and future challenges - Erstad, Ola; Eickelmann, Birgit; Eichhorn, Koos (Education and Information Technologies)

Schulische Prädiktoren für die Nutzung neuer Technologien im Mathematikunterricht der Primarstufe und ihre Zusammenhänge mit Schülerkompetenzen - Eickelmann, Birgit; Gerick, Julia; Bos, Wilfried (IGLU & TIMSS. 10 Jahre international vergleichende Schulleistungsforschung in der Grundschule. Vertiefende Analysen zu IGLU und TIMSS 2001 bis 2011)

Wie geht es weiter? Zentrale Befunde der Studie ICILS 2013 und mögliche Handlungs- und Entwicklungsperspektiven für Einzelschulen - Eickelmann, Birgit; Bos, Wilfried; Gerick, Julia (SchulVerwaltung NRW)

Implementierung eines hybriden Verschlüsselungsverfahrens nach Cramer und Shoup - Kalde, Benedikt

Total digital? - Wie Jugendliche Kompetenzen im Umgang mit neuen Technologien erwerben. Dokumentation der Analysen des Vertiefungsmoduls zu ICILS 2013 - Eickelmann, Birgit; Bos, Wilfried; Vennemann, Mario

Tackling Educational Challenges in a Digitally Networked World - Lai, Kwok-Wing; Davis, Niki; Eickelmann, Birgit; Erstad, Ola; Fisser, Petra; Gibson, David C.; Khaddage, Ferial; Knezek, Gerald; Webb, Mary (KEYCIT 2014. Key Competencies in Informatics and ICT)

Singulärwertzerlegung für μ-ähnliche Bregman-Divergenzen - Strotmann, Daniela

HybridTE: Traffic Engineering for Very Low-Cost Software-Defined Data-Center Networks - Wette, Philip; Karl, Holger (Proceedings of the 4th European Workshop on Software Defined Networks (EWSDN 2015))
The size of modern data centers is constantly increasing. As it is not economic to interconnect all machines in the data center using a full-bisection-bandwidth network, techniques have to be developed to increase the efficiency of data-center networks. The Software-Defined Network paradigm opened the door for centralized traffic engineering (TE) in such environments. Up to now, there were already a number of TE proposals for SDN-controlled data centers that all work very well. However, these techniques either use a high amount of flow table entries or a high flow installation rate that overwhelms available switching hardware, or they require custom or very expensive end-of-line equipment to be usable in practice. We present HybridTE, a TE technique that uses (uncertain) information about large flows. Using this extra information, our technique has very low hardware requirements while maintaining better performance than existing TE techniques. This enables us to build very low-cost, high performance data-center networks.

IT-Unterstützung in Emergency Management & Response - Erfurth, Christian; Pottebaum, Jens (45. Jahrestagung der Gesellschaft für Informatik, Informatik 2015, Informatik, Energie und Umwelt, 28. September - 2. Oktober 2015 in Cottbus, Deutschland)
Keywords: Ver{\

Towards Establishing Monotonic Searchability in Self-Stabilizing Data Structures - Scheideler, Christian; Setzer, Alexander; Strothmann, Thim Frederik (Proceedings of the 19th International Conference on Principles of Distributed Systems (OPODIS))
Distributed applications are commonly based on overlay networks interconnecting their sites so that they can exchange information. For these overlay networks to preserve their functionality, they should be able to recover from various problems like membership changes or faults. Various self-stabilizing overlay networks have already been proposed in recent years, which have the advantage of being able to recover from any illegal state, but none of these networks can give any guarantees on its functionality while the recovery process is going on. We initiate research on overlay networks that are not only self-stabilizing but that also ensure that searchability is maintained while the recovery process is going on, as long as there are no corrupted messages in the system. More precisely, once a search message from node u to another node v is successfully delivered, all future search messages from u to v succeed as well. We call this property monotonic searchability. We show that in general it is impossible to provide monotonic searchability if corrupted messages are present in the system, which justifies the restriction to system states without corrupted messages. Furthermore, we provide a self-stabilizing protocol for the line for which we can also show monotonic searchability. It turns out that even for the line it is non-trivial to achieve this property. Additionally, we extend our protocol to deal with node departures in terms of the Finite Departure Problem of Foreback et. al (SSS 2014). This makes our protocol even capable of handling node dynamics.

Towards a Universal Approach for the Finite Departure Problem in Overlay Networks - Koutsopoulos, Andreas; Scheideler, Christian; Strothmann, Thim Frederik (Proceedings of the 17th International Symposium on Stabilization, Safety, and Security of Distributed Systems (SSS))
A fundamental problem for overlay networks is to safely exclude leaving nodes, i.e., the nodes requesting to leave the overlay network are excluded from it without affecting its connectivity. There are a number of studies for safe node exclusion if the overlay is in a well-defined state, but almost no formal results are known for the case in which the overlay network is in an arbitrary initial state, i.e., when looking for a self-stabilizing solution for excluding leaving nodes. We study this problem in two variants: the Finite Departure Problem (FDP) and the Finite Sleep Problem (FSP). In the FDP the leaving nodes have to irrevocably decide when it is safe to leave the network, whereas in the FSP, this leaving decision does not have to be final: the nodes may resume computation when woken up by an incoming message. We are the first to present a self-stabilizing protocol for the FDP and the FSP that can be combined with a large class of overlay maintenance protocols so that these are then guaranteed to safely exclude leaving nodes from the system from any initial state while operating as specified for the staying nodes. In order to formally define the properties these overlay maintenance protocols have to satisfy, we identify four basic primitives for manipulating edges in an overlay network that might be of independent interest.

The impact of communication patterns on distributed locally self-adjusting binary search trees - Strothmann, Thim Frederik (Proceedings of the 9th International Workshop on Algorithms and Computation (WALCOM))
This paper introduces the problem of communication pattern adaption for a distributed self-adjusting binary search tree. We propose a simple local algorithm, which is closely related to the nearly thirty-year-old idea of splay trees and evaluate its adaption performance in the distributed scenario if different communication patterns are provided.To do so, the process of self-adjustment is modeled similarly to a basic network creation game, in which the nodes want to communicate with only a certain subset of all nodes. We show that, in general, the game (i.e., the process of local adjustments) does not converge, and convergence is related to certain structures of the communication interests, which we call conflicts.We classify conflicts and show that for two communication scenarios in which convergence is guaranteed, the self-adjusting tree performs well.Furthermore, we investigate the different classes of conflicts separately and show that, for a certain class of conflicts, the performance of the tree network is asymptotically as good as the performance for converging instances. However, for the other conflict classes, a distributed self-adjusting binary search tree adapts poorly.

The complexity of pure equilibria in mix-weighted congestion games on parallel links - Monien, Burkhard; Mavronicolas, Marios (Information Processing Letters)
We revisit the simple class of weighted congestion games on parallel links [10], where each player has a non-negative weight and her cost on the link she chooses is the sum of the weights of all players choosing the link. We extend this class to mix-weighted congestion games on parallel links, where weights may as well be negative. For the resulting simple class, we study the complexity of deciding the existence of a pure equilibrium, where no player could unilaterally improve her cost by switching to another link.We show that even for a singlenegative weight, this decision problem is strongly NP-complete when the number of links is part of the input; the problem is NP-complete already for two links. When the number of links is a fixed constant, we show, through a pseudopolynomial, dynamic programming algorithm, that the problem is not strongly NP-complete unless P = NP; the algorithm works for any number of negative weights.

Systematically Deriving Quality Metrics for Cloud Computing Systems - Becker, Matthias; Lehrig, Sebastian; Becker, Steffen (Proceedings of the 6th ACM/SPEC International Conference on Performance Engineering)
In cloud computing, software architects develop systems for virtually unlimited resources that cloud providers account on a pay-per-use basis. Elasticity management systems provision these resources autonomously to deal with changing workload. Such changing workloads call for new objective metrics allowing architects to quantify quality properties like scalability, elasticity, and efficiency, e.g., for requirements/SLO engineering and software design analysis. In literature, initial metrics for these properties have been proposed. However, current metrics lack a systematic derivation and assume knowledge of implementation details like resource handling. Therefore, these metrics are inapplicable where such knowledge is unavailable.To cope with these lacks, this short paper derives metrics for scalability, elasticity, and efficiency properties of cloud computing systems using the goal question metric (GQM) method. Our derivation uses a running example that outlines characteristics of cloud computing systems. Eventually, this example allows us to set up a systematic GQM plan and to derive an initial set of six new metrics. We particularly show that our GQM plan allows to classify existing metrics.

Bonding of Wood Plastic Composites (WPC) - Material and Surface Modification for Special Applications - Moritzer, Elmar; Hopp, Matthias (68th Annual Assembly of the International Institute of Welding (IIW))

Kleben von Wood-Plastic-Composites (WPC) - Material- und Oberflächenmodifizierung für spezielle Anwendungen - Moritzer, Elmar; Hopp, Matthias (Jahresmagazin Kunststofftechnik)

Systematic Development and Re-Use of Model Tranformations - Besova, Galina

SynRace: Decentralized Load-Adaptive Multi-path Routing without Collecting Statistics - Schwabe, Arne; Karl, Holger (Proceedings of the 4th European Workshop on Software Defined Networks (EWSDN 2015))
Multi-rooted trees are becoming the norm for modern data-center networks. In these networks, scalable flow routing is challenging owing to vast number of flows. Current approaches either employ a central controller that can have scalability issues or a scalable decentralized algorithm only considering local information. In this paper we present a new decentralized approach to least-congested path routing in software-defined data center networks that has neither of these issues: By duplicating the initial (or SYN) packet of a flow and estimating the data rate of multiple flows in parallel, we exploit TCP’s habit to fill buffers to find the least congested path. We show that our algorithm significantly improves flow completion time without the need for a central controller or specialized hardware.

Reputation und Vertrauen auf Online-Märkten - Sonntag, Melissa